A Design of Cloud-Based Billing and Monitoring System for an Electric Company - Enriquez, John Benedic R. (International Journal of Computing Sciences Research, 2018)
Purpose – This descriptive study developed a cloud-based billing and monitoring system for an electric company named Quezelco1. The developed system was implemented in a web-based environment using a third party cloud infrastructure. After the development, the study gathered feedback from both end-users and technical experts to evaluate the proposed system in terms of content, functionality, reliability, maintainability, and features. Their comments and suggestions on the proposed system were also gathered. Method – Interviews with the head of Consumer Area Department (CAD) head, IT personnel and Area Manager who fully understand the transactions and processes in electric billing of the company revealed that there was a need for an electric billing and monitoring system. After the software was developed, a questionnaire was utilized to necessary information on developing a system, and surveys to gather comments and suggestions from the respondents. The developed software was evaluated by the end-users; while the administrator page was assessed by the technical experts. Results – All items of software criteria had at least acceptable ratings (Content: End-users, M = 4.42, Technical Expert, M = 4.42 = 4.32; Functionality:  End-users, M = 4.42 = 4.47, Technical Expert, M = 4.42 = 4.49; Reliability: End-users, M = 4.42 = 4.40, Technical Expert, M = 4.42 = 4.42; Maintainability: End-users, M = 4.42 = 4.46, Technical Expert, M = 4.42 = 4.47; Features: End-users, M = 4.42 = 4.57, Technical Expert, M = 4.42 = 4.58). Test of difference between means revealed that there are no significant differences on the ratings of end-users and technical experts. Conclusion/Recommendations – They both viewed the software acceptable. It was recommended that mobile payments (e.g., PayPal and credit cards) be included in future researches. There was also a need to enhance the customer experience online; promote other better support channel aside from phone calls, regular snail mails, and SMS. This study had shown that that cloud-based framework can be utilized as a tool for improving basic services in terms billing and monitoring. Practical Implication – This study can be replicated in other basic services (e.g., water services) or in other fields of business (e.g., education or bank).